2020
DOI: 10.1136/bmjopen-2020-039017
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-method evaluation of CARITAS: a hospital-to-community model of integrated care for dementia

Abstract: ObjectivesThe capability and capacity of the primary and community care (PCC) sector for dementia in Singapore may be enhanced through better integration. Through a partnership involving a tertiary hospital and PCC providers, an integrated dementia care network (CARITAS: comprehensive, accessible, responsive, individualised, transdisciplinary, accountable and seamless) was implemented. The study evaluated the process and extent of integration within CARITAS.DesignTriangulation mixed-methods design and analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…A mixed-method approach is well suited to study complexity interventions 28 and the complex adaptive systems to which they are applied. Mixed-method approaches have been used to study information flow and organisational networks, 29 integration of organisational interventions, 30 31 effectiveness of service models, 32 and how health information technology affects communication, 33 patient monitoring, 34–36 care provision 37 and clinical decision making. 38 …”
Section: Methods and Analysismentioning
confidence: 99%
“…A mixed-method approach is well suited to study complexity interventions 28 and the complex adaptive systems to which they are applied. Mixed-method approaches have been used to study information flow and organisational networks, 29 integration of organisational interventions, 30 31 effectiveness of service models, 32 and how health information technology affects communication, 33 patient monitoring, 34–36 care provision 37 and clinical decision making. 38 …”
Section: Methods and Analysismentioning
confidence: 99%
“…The six key domains provide a framework to characterize the degree of integration from a multifocal perspective. The literature suggests that the RMIC has been well applied to explore and analyse the integration perspectives of different stakeholders’ at different levels in various study settings including Australia [ 19 ], Norway [ 20 ], Singapore [ 21 ], China [ 22 23 24 25 ], etc. Furthermore, Chen Z 2019 have already explored and validated the RMIC in China’s context, which confirmed its adaptation and applicability in China particularly regarding the key domains covered in this model [ 25 ].…”
Section: Theory and Methodsmentioning
confidence: 99%
“…A handful of programmes described a focus on lowering hospital resource utilisation by supporting patients during care transitions (36%) [28,31,39,42,43,45,46,50,55,56], and facilitating referrals from the specialist outpatient clinics (SOCs) to primary care providers (PCPs) (18%) [28,39,40,51,54]. The remaining 13 articles (46%) aimed to optimise the management of specific chronic diseases [29,[31][32][33][34][35]37,45,46,49,50,52,53]. Importantly, heightened emphasis on reducing hospital resource utilisation and facilitating care transitions to lower levels of care aligns with the local vision of shifting care Beyond Hospital to Community.…”
Section: Operational Characteristics Of Programmes Reviewedmentioning
confidence: 99%
“…Half of the articles reviewed depicted off-site care delivery [30,32,36,38,[41][42][43][44]47,48,[51][52][53]55], nine in the hospital setting [29,31,39,40,45,46,49,50,54] and three in primary care settings [34,35,37]. Only Ang et al and Ha et al, reported care delivery occurring in both hospital and primary care settings under the same respective programme [28,33].…”
Section: Operational Characteristics Of Programmes Reviewedmentioning
confidence: 99%
See 1 more Smart Citation